1, 25(OH)2D3 induces regulatory T cell differentiation by influencing the VDR/PLC-γ1/TGF-β1/pathway. (November 2017) - Zhou, Qiang; Qin, Shengying; Zhang, Jinyan; Zhon, Lin; Pen, Zhihai; Xing, Tonghai
Highlights: 1, 25(OH)2 D3 induces regulatory T cells, while suppressing the differentiation of Th17 cells in Jurkat E clone 6, 1 cells. 1, 25(OH)2 D3 induces expression of cytokines TGF-β1, and inhibits the secretion of pro-inflammatory cytokines IL-17A. 1, 25(OH)2 D3 upregulates the expression of PLC-γ1 and TGF-β1. PLC-γ1 is involved in inducing TGF-β1 gene coding. 1, 25(OH)2 D3 induces the Tregs differentiation through modulating VDR/PLC-γ1/TGF-β1 pathway. Abstract: Vitamin D has been recommended as an immune modulator in recent years, in addition to regulating calcium-phosphorous-bone metabolism. Clinical studies on organ transplantation found that vitamin D sufficiency patients were less likely to develop acute cellular rejection within one year after transplantation compared to those with vitamin D deficiency. Thus, a high percentage of regulatory T cells might play a key role in preventing acute cellular rejection (ACR). In this report, we studied the specific effects of 1, 25(OH)2D3 on human T cell diﬀ ;erentiation, and determined the potential molecule mechanism behind. Results showed that 1, 25(OH)2D3 induced the differentiation of T-regulatory cells (Treg cells), while inhibiting Th17 cell proliferation. In addition, 1, 25(OH)2D3 promoted secretion of the anti-inflammatory cytokine, transforming Growth Factor beta1 (TGF-β1) but suppressed pro-inflammatory cytokines such as interleukin-17 (IL-17). Phospholipase C gamma 1 (PLC-γ1) is an indispensable signaling protein downstream of the classical TCR signaling pathway and was shown to play a crucial role in T cell activation, while Naive T cells expressed less PLC-γ1. Here we showed that Vitamin D could significantly upregulate PLC-γ1 expression, which then induced expression of TGF-β1. In summary, 1, 25(OH)2D3 indirectly modulates the differentiation of Treg/Th17 cells by aﬀ ;ecting the VDR/PLC-γ1/TGF-β1pathway. These results indicate that administration 1, 25(OH)2D3 supplements may be a beneficial treatment for organ transplantation recipients.